2014
DOI: 10.3390/ijms16010758
|View full text |Cite
|
Sign up to set email alerts
|

Motor, Visual and Emotional Deficits in Mice after Closed-Head Mild Traumatic Brain Injury Are Alleviated by the Novel CB2 Inverse Agonist SMM-189

Abstract: We have developed a focal blast model of closed-head mild traumatic brain injury (TBI) in mice. As true for individuals that have experienced mild TBI, mice subjected to 50–60 psi blast show motor, visual and emotional deficits, diffuse axonal injury and microglial activation, but no overt neuron loss. Because microglial activation can worsen brain damage after a concussive event and because microglia can be modulated by their cannabinoid type 2 receptors (CB2), we evaluated the effectiveness of the novel CB2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
123
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(141 citation statements)
references
References 86 publications
(142 reference statements)
16
123
2
Order By: Relevance
“…We have, in fact, shown that targeting microglia via their type-2 cannabinoid receptors (CB2) with a CB2 receptor inverse agonist can reduce the motor, visual, and behavioral deficits and the brain, spinal cord, and retinal injury seen after 50-psi blast injury. 110 Comparison with open-skull rodent models Many studies have used lateral fluid percussion, weight drop, or controlled piston impact to the exposed dura in rats or mice, which causes necrotic brain destruction at the site of impact, thereby modeling severe TBI. 8,10,11,[13][14][15][16][17][18] In addition to the neuron loss at the impact site, these approaches commonly yield subdural hemorrhage, brain vascular damage, microglial activation, and axonal injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have, in fact, shown that targeting microglia via their type-2 cannabinoid receptors (CB2) with a CB2 receptor inverse agonist can reduce the motor, visual, and behavioral deficits and the brain, spinal cord, and retinal injury seen after 50-psi blast injury. 110 Comparison with open-skull rodent models Many studies have used lateral fluid percussion, weight drop, or controlled piston impact to the exposed dura in rats or mice, which causes necrotic brain destruction at the site of impact, thereby modeling severe TBI. 8,10,11,[13][14][15][16][17][18] In addition to the neuron loss at the impact site, these approaches commonly yield subdural hemorrhage, brain vascular damage, microglial activation, and axonal injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we recently described the benefits of reducing neuroinflammation in our TBI model. 110 Finally, the injury produced with our focal blast model can be compared with that resulting from focal mechanical impact to the same head location. The forces associated with blast and with mechanical impact are similar in duration and could readily be adjusted to be similar in magnitude and in the minimal amount of head movement that occurs.…”
Section: Discussionmentioning
confidence: 99%
“…44 Based on the potential of CB2 inverse agonist in treating CNS diseases, we demonstrated that SMM-189 beneficially down-regulates cytokine and chemokine production in LPS stimulated primary human microglia. 25,44 Subsequent testing of SMM-189 in the murine model of mild traumatic brain injury (mTBI), and pre-clinical evaluation of biopharmaceutical properties, demonstrated the protective effects of SMM-189 in mTBI and indicated that the 2,6-dihydroxy-biphenyl-aryl-methanone scaffold has acceptable drug-like properties to warrant further investigation. 25 The potential of the scaffold for developing selective CB2 inverse agonist prompted us to investigate the functional group requirements required for activity.…”
Section: Figure 1 Structures Of Selected Cb2 Inverse Agonistsmentioning
confidence: 99%
“…25,44 Subsequent testing of SMM-189 in the murine model of mild traumatic brain injury (mTBI), and pre-clinical evaluation of biopharmaceutical properties, demonstrated the protective effects of SMM-189 in mTBI and indicated that the 2,6-dihydroxy-biphenyl-aryl-methanone scaffold has acceptable drug-like properties to warrant further investigation. 25 The potential of the scaffold for developing selective CB2 inverse agonist prompted us to investigate the functional group requirements required for activity. A set of compounds were synthesized and evaluated for CB1 and CB2 receptor binding in ACTOne membrane preparations and functional activity using the ACTOne cAMP assay.…”
Section: Figure 1 Structures Of Selected Cb2 Inverse Agonistsmentioning
confidence: 99%
See 1 more Smart Citation